THE US HIGHER EDUCATION: SYSTEM’S INSTITUTIONAL VALUES - Iryna Reheilo (Неперервна професійна освіта: теорія та практика, 2019)
The world-class universities value orientations are enlightened according to the results of analysing the US regulations. It is grounded that Research University is the most advanced form of generating new knowledge based on education and research integrity. It is established that research universities have a significant socio-economic impact by creating innovative technologies, reforming the US and world economy and a significant impact on the development of nation’s human capital, which is reflected, in particular, in the leaders’ training – the professionals oriented on the American society welfare growth. The institutional values of the US doctoral / research universities according to the Carnegie Classification of Institutions of Higher Education are revealed. The Association of American Universities values are found out, among them: institutional autonomy, which is based on public trust, academic freedom as an expression of independence and responsibility, shared governance, which is held collegially by all participants of educational process. The value principles of the American Council of Education are presented, among them: inclusion of all stakeholders based on mutual respect; excellence in providing quality educational services; innovation, that is crosscutting in all areas of institutional activity; cooperation through strategic partnerships; and impact that is being made through the modernization of society. The overall quantitative characteristics of the US research universities activities results are given, which, based on these value principles, are the model of the highest world standards achievement and continuously demonstrate the desire to improve the quality of life of people and society as a whole.